2019
DOI: 10.1111/josh.12780
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Health Education Teacher Characteristics on Students' Health‐Related Knowledge Gains

Abstract: BACKGROUND:Studies have examined relationships between teacher characteristics and student achievement in courses such as math and science. This study is among the first to examine effects of teacher characteristics on student knowledge in a health course. METHODS:Student (N = 6143) pretest and posttest data were linked to teacher (N = 67) data. Changes in student knowledge scores from pre-to postcourse were explored using mixed-effects linear models. Teacher characteristics included professional development (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…Furthermore, future research could be helpful in identifying potential roles of teacher and classroom characteristics in differential knowledge gains among student subgroups. A previous analysis from this district of knowledge gains for health education broadly (not just SHE topics) found that certain teacher characteristics (e.g., certification to teach health, having a dedicated classroom, having attended more professional development) were associated with greater knowledge gains among students [25]. When looking at SHE specifically, previous qualitative studies from this district found that certain class (e.g., having a dedicated classroom, having sufficient time) and teacher characteristics (e.g., gender, receiving professional development) impacted teacher confidence in implementing SHE [23,24].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, future research could be helpful in identifying potential roles of teacher and classroom characteristics in differential knowledge gains among student subgroups. A previous analysis from this district of knowledge gains for health education broadly (not just SHE topics) found that certain teacher characteristics (e.g., certification to teach health, having a dedicated classroom, having attended more professional development) were associated with greater knowledge gains among students [25]. When looking at SHE specifically, previous qualitative studies from this district found that certain class (e.g., having a dedicated classroom, having sufficient time) and teacher characteristics (e.g., gender, receiving professional development) impacted teacher confidence in implementing SHE [23,24].…”
Section: Discussionmentioning
confidence: 87%
“…The study was reviewed and approved by ICF's Institutional Review Board and the district's Research Review Office. Other findings including those related to district-provided SHE supports [23], teachers' and students' perceptions and experiences with SHE [24], and associations between teacher characteristics and students' health-related (not specifically sexual health) knowledge gains [25] have been previously reported. The purpose of this study is to present findings related to sexual health knowledge and sexual behaviors among students following implementation of enhanced district support for SHE.…”
Section: Introductionmentioning
confidence: 74%
“…For example, academic preparation and licensure in health education can help to ensure comfort with health-related topics and skills and confidence in facilitating student performance. 24,36,37 Research by Murray et al corroborates this characteristic by documenting empirical relationships between teacher certification and improvements in student health-related knowledge gains, 38,39 underscoring the importance of formal preparation in health education. A health education teacher's understanding or and belief that health and learning are connected is also crucial to their developing competency.…”
Section: Personal Characteristics Domainmentioning
confidence: 95%
“…A literatura consultada sobre a relação entre o tempo de experiência docente e o desempenho acadêmico indica achados conflitantes. Enquanto Murray et al (2019) e Çakir e Bichelmeyer (2013) não encontraram associação significante entre o tempo de experiencia docente e o ganho no desempenho, Darling-Hammond (2000) e Clotfelter, Ladd e Vigdor (2007) obtiveram evidências de que há relação positiva. Conforme os achados deste estudo, professores mais experientes e menos experientes tendem a usar métodos de ensino similares.…”
Section: Método Pública (N = 37) Privada (N = 42) Valor P (Bicaudal) Médiaunclassified
“…O contexto do ensino de contabilidade é marcado por perspectiva ancorada no que se denomina de abordagem tradicional, o que coloca uma série de implicações específicas para o processo de ensino e aprendizagem (DELLAPORTAS, 2015;MIZUKAMI, 2016). Dellaportas (2015) aponta que enquanto a educação contábil tem requerido ênfase no ensino que privilegie o desenvolvimento de habilidades sociais com aplicação de atividades pedagógicas inovadoras, as pesquisas continuam indicando que o ensino que se pratica permanece inalterado em sua essência, privilegiando a racionalidade técnica, limitando o desenvolvimento do conhecimento contábil sob as perspectivas crítica, social e política.…”
Section: Introductionunclassified